Evolution and Gene Flow of Azole Resistance and Other Virulence Factors in Aspergillus fumigatus - Alghamdi, Asmaa; Alghamdi, Asmaa (2022)
Aspergillus fumigatus is a commonly encountered fungus in the environment and has a primary ecological role as a saprotroph in the breakdown and recycling of organic matter. It is also an opportunistic pathogen and the major cause of invasive aspergillosis (IA) in humans, especially in immunocompromised individuals. The main method of treatment of infection is the use of azole antifungals. However, the past twenty years has seen an ever-increasing appearance of resistance to azole antifungals in isolates of A. fumigatus from both clinical and environmental settings. Therefore, the overall theme of work in this thesis was to increase our understanding about the genetic basis of both azole resistance and pathogenicity in this fungus. Previous studies have shown that azole resistance in A. fumigatus is frequently linked to mutations in the cyp51A gene. However, a number of azole resistant isolates have been reported to exhibit non-cyp51A based form of resistance. Therefore, exploring the genetic basis of azole resistant in such isolates, in which the genetic basis of resistance is unknown, is required to develop better diagnostic methods for improved disease treatment. A total of 32 isolates from clinical and environmental sources, with supposed non-cyp51A high levels of azole resistance, were obtained from collaborating groups. Screening with E-tests revealed that half of the isolates showed low or unstable levels of resistance. The remaining 16 isolates were screened for known resistant mechanisms. Six isolates showed known cyp51A-based resistant mechanisms. However, an apparently novel form of azole resistance was detected in eight clinical isolates based on the presence of a relatively large tandem repeat in the cyp51A promotor region. These isolates were assigned for further analysis. In addition, one of the two remaining isolates (C286) that exhibited a non-cyp51A based form of azole resistance, with unknown resistance mechanism(s), was chosen as a candidate for later bulk segregant analysis. Further analysis of the eight clinical isolates showing an expansion in size of the cyp51A promoter region revealed the presence of a four-fold tandem repeat in six isolates, a three-fold tandem repeat in one isolate and a two-fold tandem repeat in one isolate of the same 130 bp sequence, here termed TR130. The presence of TR130 was found to be correlated with elevated resistance to both itraconazole and voriconazole, with the extent of resistance in proportion to the number of tandem repeats. Sexual crossing also demonstrated a direct correlation between the presence of TR130 and azole resistance. Furthermore, gene expression studies revealed a significant increase in cyp51A expression in isolates harbouring TR130, which was correlated with the number of repeats and the level of azole resistance. Gene manipulation studies were then conducted, with different number of repeats of TR130 introduced into a wild-type (WT) sensitive lab strain. Transformants showed greatly increased resistance to itraconazole, in proportion to the number of TR130 repeats introduced, and also showed concomitant increases in cyp51A expression. Azole sensitivity was restored in a complement strain in which TR130 repeat was removed. Thus, results demonstrated that the TR130 mutation can lead to azole resistance. Moreover, infection of Galleria mellonella was used to evaluate the treatment efficiency of A. fumigatus strains harbouring different forms of TR130. No significant differences in virulence were observed between TR130 and WT isolates. By contrast, itraconazole treatment was less efficient in the control of strains harbouring TR130 than WT strains, indicating the likely clinical significance of A. fumigatus strains harbouring different forms of the TR130. The evolutionary origins of the TR130 repeat are discussed based on phylogenetic analysis. Sexual crossing of the azole resistant isolate C286 with sensitive partners revealed a 1:1 segregation pattern of resistance: sensitivity, consistent with monogenic inheritance. BSA was then undertaken in conjunction with next generation sequencing of parents and progeny pools. Three rounds of backcrossing were performed to increase isogeneity of progeny. DNA was then extracted from the parents and progeny pools of 100 resistant and 100 sensitive progeny. DNA was genome sequenced and a BSA bioinformatic pipeline used to identify variants between the azole resistant parent and progeny, and the sensitive parent and progeny pools. This BSA pipeline had recently been used successfully to identify a single linked region of the genome containing a causal mutation of azole resistance in A. fumigatus. A total of 636 SNPs and 57 INDELs were found that varied between the azole resistant and sensitive groups. However, unlike the previous study there was no clear single linked region containing these variants so no definitive answer as to the resistant mechanisms as yet. In addition, the sexual cycle of A. fumigatus was exploited to investigate the genetic basis of a novel form of oxidative stress response observed in the fungus, together with aspects of the population biology of the species. Previous studies had identified clinical isolates with a striking phenotype linked to pathogenicity relating to the ability to grow in a low oxygen environment and/or under oxidative stress produced from reactive oxygen species (ROS) compounds. Crosses were set up between isolates exhibiting and lacking this phenotype, and progeny screened under oxidative stress conditions. Results showed that progeny exhibited a wide variety of morphologies, indicating that the phenotype has a polygenic basis linked to more than one gene. Finally, there is recent evidence of two distinct clades within global populations of A. fumigatus with most azole resistant isolates clustered into one group. Crosses were set up between azole resistant isolates and highly fertile isolates from the opposing clade. Results showed successful crossing between a series of isolates under laboratory conditions, indicating no barrier to gene flow of azole resistance between the two groups.